2022
DOI: 10.1039/d2se01081j
|View full text |Cite
|
Sign up to set email alerts
|

Pre-lithiated Li4+xTi5O12 (0 ≤ x ≤ 3) anodes towards building high-performance Li-ion capacitors

Abstract: Spinel Li4Ti5O12 is an extensively studied and successfully commercialized battery type electrode for Lithium-ion capacitor (LIC), mainly due to its abundance, improved rate capability, and safety guaranteed by the high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Pre-lithiation is considered an excellent method to nullify the sudden cell voltage drop/rise during the charge/discharge process in the LTO anode and compensate for the energy loss during the initial cycle that is due to the high initial potential of the AC cathode in LICs. [13] Divya et al [14] studied the role of the pre-lithiation of LTO in LICs by varying the prelithiation levels (Li 4+x Ti 5 O 12 , 0 ≤ x ≤ 3). They concluded that the pre-lithiation step is not crucial for the assembly of LICs.…”
Section: Lto Anodementioning
confidence: 99%
See 2 more Smart Citations
“…Pre-lithiation is considered an excellent method to nullify the sudden cell voltage drop/rise during the charge/discharge process in the LTO anode and compensate for the energy loss during the initial cycle that is due to the high initial potential of the AC cathode in LICs. [13] Divya et al [14] studied the role of the pre-lithiation of LTO in LICs by varying the prelithiation levels (Li 4+x Ti 5 O 12 , 0 ≤ x ≤ 3). They concluded that the pre-lithiation step is not crucial for the assembly of LICs.…”
Section: Lto Anodementioning
confidence: 99%
“…Figure 2. (a) Comparison of CV profiles of all four LICs at a scan rate of 1 mV s −1 .Reprinted with permission [14]. Copyright 2022, Royal Society of Chemistry, (b) anode and cathode voltage profiles of asymmetric cells with AC/LTO mass ratios of 4.17, 1.54, and 0.72 at a 10 C rate, (c) capacity retention at 10 C over 1000 cycles for the three asymmetric systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main issue with LICs is balancing the kinetics of a slower-rate LIBtype electrode and a faster-rate EDLC-type electrode. [1][2][3][4][5][6][7][8][9] In conventional LICs, the Li + ions from the electrolyte salts are inserted into the battery-type electrode, and PF 6 − adsorption occurs on the surface of the capacitive carbon cathode during charging. On discharge, the reverse process occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The main issue with LICs is balancing the kinetics of a slower-rate LIB-type electrode and a faster-rate EDLC-type electrode. 1–9…”
Section: Introductionmentioning
confidence: 99%